Impact of Ozone Treatment on Seed Germination - A Systematic Review - Pandiselvam, R.; Mayookha, V.P.; Kothakota, Anjineyulu; Sharmila, L.; Ramesh, S.V.; Bharathi, C.P.; Gomathy, K.; Srikanth, V. (Ozone: science & engineering, 2020)
Rising world population necessarily increases the food requirement. At the same time, agricultural land has been reduced drastically due to the rapid urbanization and industrialization which severely affects the land availability for the growers. However, the enhancement of seed germination has the potential to secure the food safety of masses by improving crop production. The traditionally followed chemical methods to improve seed germination have major limitations including being environmentally unhealthy, time-consuming, and are labor-intensive. Of late the application of ozone on plant growth and seed germination has attained greater significance. This promising technique and its various potential applications in the food industry have started emerging. Ozone is a strong antimicrobial agent as well as a germination enhancer. Ozone, in limited quantity, enhances seed germination rate; on the other hand, excess ozone can also cause some negative effects. Generally, ozone is applied either in gaseous or aqueous phases; however, the method and treatment conditions of ozone vary with the subject samples. This review mainly discusses the impact of ozone treatment on seed germination, the quality changes that accompany the treatment as well as the factors affecting the efficiency of ozone.